Tipologi Batang Tubuh Pisau Tumbuk Lada: Sebuah Analisis Makna pada Pusaka Melayu - Amelia, Pidia; Lukitaningsih, Lukitaningsih; Purnamasari, Ika (Mahesa Research Center (PT. Mahesa Global Publishing), 2023)
This article discusses the meaning contained in the body of a Malay heritage weapon called the